Terapi Peregangan Otot Pernafasan untuk Kapasitas Vital Paru Pasien Asma - Y Yunani; Amrih Widiati; M Jamaluddin (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2018)
Asthma caused dyspnea because bronchospasme. Expiration rate andinspiration volume decrease, it will reduce pulmonary vital capacity.Asthma patient need exercise to improve pulmonary vital capacity. Therespiratory muscle stretching will strengthen and endurancerespiratory muscles. The objective of the study was to know the effectof respiratory muscle stretching toward pulmonary vital capacity ofasthma patient. These study used quantitative study with quasyexperiment by using randomized pretest posttest design. Interventiongroup used respiratory muscle stretching and control group used deepbreathing exercise. The sample was 15 respondents for interventiongroup and 15 respondents for control group. The instruments werespirometry and observation sheet. Data analysis used T paired test andMann Whitney test by hypothesis test with α 0.05. The mean differencebetween two groups used Mann Whitney test, where p value was 0.001.Respiratory muscle stretching more efective to increase pulmonaryvital capacity.